The Effect of Providing Health Education on Knowledge About Cinnamon for Reducing Blood Sugar Levels in Diabetes Mellitus Sufferers in Sumengko Village Sukomoro District Nganjuk Regency - Sony Wahyu Tri Cahyono; Oktaffrastya W. Septafani; Yolanda Herlinasari (Journal for Research in Public Health, 2025)
Diabetes Mellitus is a chronic disease characterized by excessive blood sugar levels which can result in long-term complications. One non-pharmacological treatment with herbal plants is cinnamon. In general, many people do not know how to understand the use of medicinal plants as anti-diabetics. This research aims to determine the effect of providing health education on knowledge about cinnamon for reducing blood sugar levels in diabetes mellitus sufferers in Sumengko Village, Sukomoro District, Nganjuk Regency. The design of this research was pre-experimental with a pre-posttest design with one group (One Group Pre-Post Test Design) which was carried out on September 5 2023 in Sumengko Village, Sukomoro District, Nganjuk Regency. Population of 68 people suffering from Diabetes Mellitus, purposive sampling technique. The sample in this study was 54 respondents. The independent variable is Health Education about cinnamon which is measured using SAP Knowledge about cinnamon for reducing blood sugar levels. The dependent variable is knowledge about cinnamon for reducing sugar levels in diabetes mellitus sufferers using the Cinnamon Knowledge questionnaire. Statistical tests use Wilcoxon ρ-value = 0.000, ρ-value ≤ a (0.05). The results obtained from 54 respondents before providing Health Education, almost all of it had insufficient knowledge, 44 respondents (81.5%). After being given Health Education, the majority had good knowledge, 32 respondents (59.3%). Wilcoxon statistical test results ρ-value = 0.000, ρ-value ≤ a (0.05). So that Ha is accepted and there is an effect of providing Health Education on Knowledge about Cinnamon for Reducing Blood Sugar Levels in Diabetes Mellitus Sufferers in Sumengko Village, Sukomoro District, Nganjuk Regency. Providing health education can increase the knowledge of Diabetes Mellitus sufferers about the use of cinnamon to control blood glucose levels.